Preparing for and responding to sexual and reproductive health in disaster settings: evidence from Fiji and Tonga - Kristen Beek; Robyn Drysdale; Matthew Kusen; Angela Dawson (BMC, 2021)
Plain Language Summary Pacific Island countries experience many disasters, including cyclones and earthquakes. The International Planned Parenthood Federation (IPPF) has been working in the Pacific to help build skills to improve the response to sexual and reproductive health (SRH) and rights during disasters. This paper describes research to identify capacity building activities that helped prepare organisations in Fiji and Tonga and how this affected the delivery of SRH during Tropical Cyclone Winston in 2016, and Tropical Cyclone Gita in 2018. Key informants in senior positions from relevant organisations were recruited and interviewed by telephone, Zoom, Skype and email. We used a framework that described different levels of capacity across phases of the disaster management cycle to analyse the data. Eight key informants described differences in Fiji and Tonga's preparedness activities before Tropical Cyclones Winston and Gita that affected the way in which services were delivered. The Tonga Family Health Association was well established as a key player in SRH service delivery before Gita and had built relationships and delivered training for disaster response to staff across a number of organisations including the Ministry of Health (MoH). These preparedness efforts facilitated a smooth and rapid response. In Fiji, the response was initially affected by a lack of training, role clarity and coordination, but linkages were quickly built to deliver care and services. Participants highlighted the importance of personal relationships, individuals' and organisations' motivation to respond, and strong links with the community to deliver SRH care. This study highlights the need for inclusive activities at individual, organisational and national levels within countries and across the Pacific region to build capacity for a SRH response.